Evaluation of Thermal State for Underground Power Cables in Nasiriya City (University of Thi-Qar Journal for Engineering Sciences, 2020)
Due to the increase in demand for electric power and increasing population density in different regions, the application of underground cables has become widely used in transmission and distribution networks. In this paper, the thermal behavior of underground cables was studied numerically. Four types of underground cables were selected copper conductor cables with (95 mm2) and (240 mm2) and aluminum conductor cables (95mm2) and (240mm2), which are used in the power networks in Iraq. The study was carried out based on the conditions surrounding such as the ambient temperature, the thermal properties of the soil and the current capacity, its effect on the thermal behavior of the cables. The results of the numerical simulation showed that the surrounding factors and loading capacities have a direct effect on determining the temperature of the cable. In addition, the type and size of the conductor cable material have an effect on determining the current-carrying capacity of the cable where the conductor cable with a nominal cross-sectional area 240mm2 has a temperature higher than the conductor cable with nominal cross-sectional 95mm2by (8.96%) for the copper conductor and (13.68%) for the aluminum conductor at current 500A.